A cold-coated zinc anticorrosive coating and its preparation process
By modifying the zinc powder and epoxy resin in the cold-coated zinc coating, the problems of poor adhesion and environmental pollution are solved, and efficient, corrosion-resistant, green and environmentally friendly coating performance is achieved.
Patent Information
- Application Number
- CN202411161926.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-08-23
AI Technical Summary
In actual applications, cold-coated zinc coatings have problems such as poor adhesion, easy shedding and foaming of coatings. At the same time, their preparation technology relies on solvent-based resins, resulting in high emissions of volatile organic compounds and polluting the environment.
By regulating the particle size, surface passivation, and introducing sulfonated polyaniline coating, combined with the water dispersion modification of the epoxy resin, a green water-based anticorrosion coating was prepared.
It significantly improves the density and corrosion resistance of the coating, enhances the shielding and protective effect and adhesion of the coating on the substrate, and reduces the emission of volatile organic compounds during preparation and application, achieving the goal of green and environmental protection.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coating preparation, and relates to a cold-coated zinc anti-corrosion coating and a preparation process thereof. Background Art
[0002] With the increase of public environmental awareness and the improvement of global energy efficiency requirements, the development of hot-dip galvanizing and hot-spray zinc technology has been gradually restricted due to its large pollution emissions and high energy consumption. In contrast, cold-applied zinc coating, as a new type of anti-corrosion material developed in response to the green development needs of modern heavy industry, uses its unique coating method to evenly cover the zinc powder on the surface of the substrate, which is an innovative surface protection technology. At present, cold-applied zinc coating is widely used in many key fields such as power infrastructure, petrochemical equipment, aviation hubs, bridge engineering, etc. due to its excellent anti-corrosion performance and simple construction and maintenance process advantages, showing significant market adaptability and technical value.
[0003] However, despite the many advantages of cold-applied zinc coatings, some challenges have also been exposed during the actual application process, mainly including the coating adhesion is not ideal, easy to fall off and blistering and other problems. In addition, the current preparation technology of cold-applied zinc coatings mainly relies on the application of solvent-based resins. This production method is inevitably accompanied by high emissions of volatile organic compounds, which can easily cause environmental pollution problems and is contrary to the current development trend of green environmental protection. These problems not only affect the long-term anti-corrosion performance of the coating, but also pose a potential threat to the safety and durability of related facilities. Therefore, in-depth exploration of the formula of new cold-applied zinc anti-corrosion coatings and their green preparation process, improving the adhesion and anti-corrosion durability between the coating and the substrate, and reducing the emission of volatile organic compounds during preparation and application have important practical significance and broad application prospects. Summary of the invention
[0004] The purpose of the present invention is to provide a cold-coated zinc anti-corrosion coating and a preparation process thereof, which has the characteristics of long-term corrosion resistance and green environmental protection.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A cold-coated zinc anti-corrosion coating, wherein the cold-coated zinc anti-corrosion coating has the following formula: by mass percentage, 70-80% of modified zinc powder, 10-20% of modified epoxy resin, 1-3% of anti-settling agent, 5-8% of curing agent, and 0.5-1% of defoaming agent.
[0007] Wherein, the preparation method of modified zinc powder is as follows:
[0008] S1.1: Grind the zinc powder in a ball mill at a speed of 600 r / min for 1 h to obtain fine zinc powder with a particle size of 500 mesh;
[0009] S1.2: Place fine zinc powder in phosphoric acid solution, ultrasonically react for 1 h, heat at 40 °C for 30 min, wash the reactant with deionized water until the pH value is 7-8, and dry at 60 °C for 12 h to obtain powder A;
[0010] S1.3: The polyaniline powder was uniformly dispersed in N,N-dimethylformamide, heated at 80 °C for 2 h to obtain solution B, chlorosulfonic acid was added to N,N-dimethylformamide, ultrasonicated for 30 min to obtain solution C, and solution C was added to solution B at a constant flow rate using a microinjection pump, wherein the mass ratio of polyaniline to chlorosulfonic acid was 2:3, heated at 80 °C for 4 h, filtered, washed with deionized water three times, and vacuum dried at 60 °C for 12 h to obtain sulfonated polyaniline powder;
[0011] S1.4: Add sulfonated polyaniline powder to the aqueous solution of powder A, wherein the mass ratio of sulfonated polyaniline powder to powder A is 1:50-60, stir evenly for 2 h, heat at 90 °C for 12 h, vacuum dry at 60 °C for 6 h, and grind with a ball mill to obtain a powder, which is the modified zinc powder.
[0012] Furthermore, the modified epoxy resin preparation method is as follows:
[0013] S2.1: Add epoxy resin to acetone, heat and mix at 60 °C for 1 h to obtain epoxy resin solution, slowly add methyl methacrylate and ammonium persulfate solution to the epoxy resin solution, wherein the volume ratio of methyl methacrylate to ammonium persulfate solution is 80-90:1, and mix by ultrasonic at 80 °C for 6 h to obtain mixture D;
[0014] S2.2: triethylamine is added to mixture D, wherein the volume ratio of triethylamine to mixture D is 1:80-100, and the mixture is stirred for 30 min. Most of the solvent is removed by vacuum distillation for 1 h to obtain reactant E;
[0015] S2.3: The reactant E is slowly added to water containing an appropriate amount of emulsifier OP-10, ultrasonically dispersed for 30 min, purified using a high-speed centrifuge at a speed of 800 r / min for 10 min, and filtered using an organic filter membrane to obtain the modified epoxy resin.
[0016] Furthermore, the anti-settling agent is natural montmorillonite with a particle size range of 0.2-0.5 μm.
[0017] Furthermore, the curing agent is a mixture of a water-based epoxy curing agent AB-HGF and a water-based epoxy curing agent AB-HGA, wherein the volume ratio of the water-based epoxy curing agent AB-HGF to the water-based epoxy curing agent AB-HGA is 2:3.
[0018] Furthermore, the defoaming agent is a polydimethylsiloxane-based defoaming agent.
[0019] Furthermore, the concentration of the phosphoric acid solution in S1.2 is 0.5 M.
[0020] Furthermore, the solution C in S1.3 is added to the solution B at a constant flow rate of 1 mL / min.
[0021] Furthermore, the concentration of the ammonium persulfate solution in S2.1 is 0.2-0.5 mg / mL.
[0022] A preparation process of a cold-coated zinc anti-corrosion coating, the specific process of the preparation process of the cold-coated zinc anti-corrosion coating is as follows:
[0023] S9.1: Add the modified epoxy resin to an appropriate amount of deionized water, stir thoroughly for 1 h to form a uniform modified epoxy resin dispersion, add an anti-settling agent to the modified epoxy resin dispersion, stir uniformly at a speed of 500 r / min for 30 min, and obtain dispersion F;
[0024] S9.2: Add the modified zinc powder to the dispersion F under stirring conditions, and continue to stir for 30 minutes to obtain a mixed solution G;
[0025] S9.3: Add the curing agent and defoaming agent to the mixed solution G according to the formula ratio, and continue stirring for 1 hour to obtain the cold-applied zinc anti-corrosion coating.
[0026] Furthermore, the stirring speed in S9.2 is 300 r / min.
[0027] The present invention significantly improves the anti-corrosion activity of zinc powder and the density of the coating by regulating the zinc powder particle size, surface passivation and introducing sulfonated polyaniline coating, and combines the water-dispersibility modification of epoxy resin to prepare a green water-based anti-corrosion coating, achieving a double leap in the anti-corrosion performance and durability of the coating.
[0028] First, the modified zinc powder, the main active ingredient in the anti-corrosion coating of the present invention, is prepared. In the present invention, the particle size of the zinc powder is first reduced and uniformed by physical ball milling, which means that the zinc powder has a larger specific surface area, so that the zinc powder can be more fully contacted and mixed with raw materials such as resin to form a more uniform and dense coating. This uniform and dense coating structure can significantly reduce the pores and defects in the coating, thereby improving the overall anti-corrosion performance of the coating. In addition, when the small-particle zinc powder contacts the corrosive medium, it can react more quickly to form a protective film and slow down the corrosion rate of the substrate. At the same time, the small-particle zinc powder also helps to enhance the adhesion and weather resistance of the coating, further improving the protective effect of the coating.
[0029] The surface of zinc powder was passivated with phosphoric acid. After being treated with 0.5 wt% phosphoric acid, a redox reaction occurred on the surface of part of the zinc powder. Zinc atoms interacted with phosphoric acid molecules to generate stable passivation products such as zinc phosphate. This process caused the originally smooth spherical zinc powder to become relatively rough in microscopic surface morphology and was evenly covered with lamellar phosphate products. These small but evenly distributed lamellar products can promote the electrical connection between the zinc powder inside the coating, so that the surface zinc powder and the zinc powder deep in the coating form a tight conductive network, enhance the conductivity of the overall structure, and optimize the performance of zinc powder as a sacrificial anode. In addition, the cross-arrangement of lamellar zinc powder and spherical zinc powder in the coating forms a dense shielding layer with excellent resistance to medium penetration, which effectively blocks the intrusion of corrosive media such as water molecules and chloride ions, and significantly improves the physical barrier effect of the coating.
[0030] Environmentally friendly and hydrophilic chlorosulfonic acid is applied to the modification of polyaniline. When the chlorosulfonic acid solution is added to the polyaniline suspension at a constant flow rate, the sulfonic acid groups in the chlorosulfonic acid molecules will undergo electrophilic substitution reactions with the hydrogen atoms on the amino or aromatic rings in the polyaniline molecules to prepare sulfonated polyaniline that can be stably dispersed in aqueous solution. Sulfonated polyaniline is introduced to the surface of zinc powder to produce a physical adsorption layer. High temperature conditions can promote the rearrangement and solidification of sulfonated polyaniline molecules on the surface of zinc powder to form a more stable adsorption layer structure. Since the sulfonic acid group has strong hydrophilicity and is easy to form stable hydrogen bonds or chemical bonds with the protected metal surface, the modified zinc powder coated with sulfonated polyaniline can be uniformly and stably dispersed in waterborne epoxy resin and firmly attached to the metal surface. In addition, sulfonated polyaniline is an excellent conductive polymer that can significantly enhance the electrochemical connection between the modified zinc powder and the metal, reduce the reaction steric hindrance, and enhance the cathodic protection of the modified zinc powder on the metal.
[0031] In addition, the epoxy resin used as the adhesive in cold-applied zinc anticorrosive coatings was modified. Using the principle of free radical polymerization, ammonium persulfate was used as an initiator to generate highly active free radicals under heating conditions. These free radicals selectively reacted with the double bonds of acrylic acid to construct polymer chains and simultaneously acted on the active aliphatic carbon sites of the epoxy resin to form a grafted structure. However, due to steric hindrance and reaction kinetics, the grafting efficiency was not complete, and the product was a mixture of ungrafted epoxy resin, grafted copolymer and polyacrylic acid. After adding water, the ungrafted components in the system spontaneously aggregated due to their insolubility in water to form a micellar structure, in which the core of the micelle was the epoxy chain segments of the ungrafted epoxy resin and the grafted copolymer, and the outer layer was composed of the carboxylate chain segments of the acrylic copolymer. The chain segments were ionized in water, giving the micelle surface charge, promoting the stable dispersion of the modified epoxy resin in water, and attracting more acrylic copolymers to coat, further strengthening the stability. Through the above steps, a water dispersion system of waterborne epoxy resin coating was successfully constructed, in which each component coexisted stably in the form of micelles and exhibited excellent dispersion properties.
[0032] Beneficial effects of the present invention:
[0033] The invention adopts phosphoric acid to modify the zinc powder, and the surface of part of the zinc powder is passivated to produce lamellar zinc phosphate material, which significantly improves the compactness of the coating and enhances the shielding protection effect of the coating on the substrate; the conductive polymer sulfonated polyaniline is introduced on the surface of the zinc powder, the electrochemical reaction impedance of the zinc powder in the coating is reduced, and the cathode protection effect of the zinc powder on the substrate is significantly enhanced; at the same time, the sulfonated polyaniline is hydrophilic and can be evenly dispersed in an aqueous epoxy resin dispersion, and the sulfonic acid group forms a hydrogen bond or a chemical bond with the metal surface, and this connection based on the strong interaction between molecules helps the anti-corrosion coating to firmly adhere to the surface of the substrate.
[0034] Acrylic monomers are grafted onto the epoxy molecular skeleton using a free radical polymerization mechanism to produce a water-based epoxy resin material that is not easily hydrolyzed and has good water dispersibility. The water-based cold-applied zinc anti-corrosion coating prepared using water-based epoxy resin uses water as a solvent and diluent, has no volatile organic compound emissions, and does not generate pollution during the preparation and construction processes. It is an environmentally friendly coating that meets national environmental protection requirements. DETAILED DESCRIPTION
[0035] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments:
[0036] Modified zinc powder 70~80%, modified epoxy resin 10~20%, anti-settling agent 1~3%, curing agent 5~8%, defoaming agent 0.5~1%,
[0037] Formula ratio 1: modified zinc powder 70%, modified epoxy resin 20%, anti-settling agent 2%, curing agent 7%, defoaming agent 1%;
[0038] Formula ratio 2: modified zinc powder 75%, modified epoxy resin 15%, anti-settling agent 2%, curing agent 7%, defoaming agent 1%;
[0039] Formula ratio 3: modified zinc powder 80%, modified epoxy resin 10%, anti-settling agent 2%, curing agent 7%, defoaming agent 1%;
[0040] Wherein, the preparation method of modified zinc powder is as follows:
[0041] S1.1: Grind the zinc powder in a ball mill at a speed of 600 r / min for 1 h to obtain fine zinc powder with a particle size of 500 mesh;
[0042] S1.2: Place fine zinc powder in 0.5 M phosphoric acid solution, ultrasonically react for 1 h, heat at 40 °C for 30 min, wash the reactant with deionized water until the pH value is 7-8, and dry at 60 °C for 12 h to obtain powder A;
[0043] S1.3: The polyaniline powder was uniformly dispersed in N,N-dimethylformamide, heated at 80 °C for 2 h to obtain solution B, chlorosulfonic acid was added to N,N-dimethylformamide, ultrasonicated for 30 min to obtain solution C, and solution C was added to solution B at a constant flow rate of 1 mL / min using a microinjection pump, wherein the mass ratio of polyaniline to chlorosulfonic acid was 2:3, heated at 80 °C for 4 h, filtered, washed with deionized water three times, and vacuum dried at 60 °C for 12 h to obtain sulfonated polyaniline powder;
[0044] S1.4: Add sulfonated polyaniline powder to the aqueous solution of powder A, wherein the mass ratio of sulfonated polyaniline powder to powder A is 1:50-60, stir evenly for 2 h, heat at 90 °C for 12 h, vacuum dry at 60 °C for 6 h, and grind with a ball mill to obtain a powder, which is the modified zinc powder.
[0045] Wherein, the preparation method of modified epoxy resin is as follows:
[0046] S2.1: Add epoxy resin to acetone, heat and mix at 60 °C for 1 h to obtain epoxy resin solution, slowly add methyl methacrylate and ammonium persulfate solution to the epoxy resin solution, wherein the volume ratio of methyl methacrylate to ammonium persulfate solution is 80-90:1, and mix by ultrasonic at 80 °C for 6 h to obtain mixture D;
[0047] S2.2: triethylamine is added to mixture D, wherein the volume ratio of triethylamine to mixture D is 1:80-100, and the mixture is stirred for 30 min. Most of the solvent is removed by vacuum distillation for 1 h to obtain reactant E;
[0048] S2.3: The reactant E is slowly added to water containing an appropriate amount of emulsifier OP-10, ultrasonically dispersed for 30 min, purified using a high-speed centrifuge at a speed of 800 r / min for 10 min, and filtered using an organic filter membrane to obtain the modified epoxy resin.
[0049] Example 1
[0050] S9.1: Add the modified epoxy resin to an appropriate amount of deionized water according to the formula ratio 1, stir thoroughly for 1 h to form a uniform modified epoxy resin dispersion, add an anti-settling agent to the modified epoxy resin dispersion, stir uniformly at a speed of 500 r / min for 30 min, and obtain dispersion F;
[0051] S9.2: Add the modified zinc powder into the dispersion F according to the formula ratio 1 under the stirring condition of 300 r / min, and continue to stir thoroughly for 30 min to obtain a mixed solution G;
[0052] S9.3: Add the curing agent and defoaming agent to the mixed solution G according to the formula ratio, and continue stirring for 1 hour to obtain the cold-applied zinc anti-corrosion coating.
[0053] Example 2
[0054] S9.1: Add the modified epoxy resin to an appropriate amount of deionized water according to the formula ratio 2, and stir thoroughly for 1 h to form a uniform modified epoxy resin dispersion. Add an anti-settling agent to the modified epoxy resin dispersion, and stir uniformly at a speed of 500 r / min for 30 min to obtain a dispersion F.
[0055] S9.2: Add the modified zinc powder into the dispersion F according to the formula ratio 2 under the stirring condition of 300 r / min, and continue to stir for 30 min to obtain a mixed solution G;
[0056] S9.3: Add the curing agent and defoaming agent to the mixed solution G according to the formula ratio, and continue stirring for 1 hour to obtain the cold-applied zinc anti-corrosion coating.
[0057] Example 3
[0058] S9.1: Add the modified epoxy resin to an appropriate amount of deionized water according to the formula ratio 3, stir thoroughly for 1 h to form a uniform modified epoxy resin dispersion, add an anti-settling agent to the modified epoxy resin dispersion, stir uniformly at a speed of 500 r / min for 30 min, and obtain dispersion F;
[0059] S9.2: Add the modified zinc powder into the dispersion F according to the formula ratio 3 under the stirring condition of 300 r / min, and continue to stir for 30 min to obtain a mixed solution G;
[0060] S9.3: Add the curing agent and defoaming agent to the mixed solution G according to the formula ratio, and continue stirring for 1 hour to obtain the cold-applied zinc anti-corrosion coating.
[0061] Comparative Example 1
[0062] In this comparative example, the modified zinc powder does not undergo the phosphoric acid reaction step, and the remaining steps are consistent with Example 1.
[0063] Comparative Example 2
[0064] In this comparative example, the modified zinc powder is not subjected to the sulfonated polyaniline modification step, and the remaining steps are consistent with those in Example 1.
[0065] Comparative Example 3
[0066] In this comparative example, zinc powder is used instead of modified zinc powder, and the remaining steps are consistent with those in Example 1.
[0067] Comparative Example 4
[0068] In this comparative example, epoxy resin is used instead of modified epoxy resin, and the remaining steps are consistent with those in Example 1.
[0069] Comparative Example 5
[0070] In this comparative example, zinc powder is used instead of modified zinc powder, epoxy resin is used instead of modified epoxy resin, and the remaining steps are consistent with Example 1.
[0071] The cold-coated zinc anti-corrosion materials of the embodiments and comparative examples were tested for salt spray resistance. The back of the sample was sealed with waterproof tape, the edges were sealed with paraffin, the coating was scratched by the cross-scratch method, and the sample was placed in a salt spray box. The test temperature was 35 ± 2 ° C, the pH was 6.5 ~ 7.5, and the spray medium was 5% sodium chloride solution. After the test, the corrosion of the sample surface was observed.
[0072] The cold-coated zinc anticorrosive materials of the embodiments and comparative examples were tested for adhesion performance. The coating surface on the test plate was bonded to the coating on another test plate by an adhesive, and the vertical stress of the coating was measured by a hydraulic method. The measured tensile force per unit area was used to represent the adhesion of the coating. The diameter of the test plate was 20 mm, and the pulling speed was 1 MPa / s.
[0073] The experimental data are summarized in the following table:
[0074]
[0075] It can be seen from the data of the examples and comparative examples that the modified zinc powder and the modified epoxy resin make the prepared cold-applied zinc anti-corrosion coating have better corrosion resistance and substrate adhesion, and have a longer-lasting protective performance for the substrate.
[0076] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A cold-applied zinc anti-corrosion coating, characterized in that: The cold-coated zinc anti-corrosion coating has the following formula: by mass percentage, modified zinc powder 70-80%, modified epoxy resin 10-20%, anti-settling agent 1-3%, curing agent 5-8%, defoaming agent 0.5-1%, Wherein, the preparation method of modified zinc powder is as follows: S1.1: Grind the zinc powder in a ball mill at a speed of 600 r / min for 1 h to obtain fine zinc powder with a particle size of 500 mesh; S1.2: Place fine zinc powder in phosphoric acid solution, ultrasonically react for 1 h, heat at 40 °C for 30 min, wash the reactant with deionized water until the pH value is 7-8, and dry at 60 °C for 12 h to obtain powder A; S1.3: The polyaniline powder was uniformly dispersed in N,N-dimethylformamide, heated at 80 °C for 2 h to obtain solution B, chlorosulfonic acid was added to N,N-dimethylformamide, ultrasonicated for 30 min to obtain solution C, and solution C was added to solution B at a constant flow rate using a microinjection pump, wherein the mass ratio of polyaniline to chlorosulfonic acid was 2:3, heated at 80 °C for 4 h, filtered, washed with deionized water three times, and vacuum dried at 60 °C for 12 h to obtain sulfonated polyaniline powder; S1.4: Add sulfonated polyaniline powder to the aqueous solution of powder A, wherein the mass ratio of sulfonated polyaniline powder to powder A is 1:50-60, stir evenly for 2 h, heat at 90 °C for 12 h, vacuum dry at 60 °C for 6 h, and grind with a ball mill to obtain a powder, which is the modified zinc powder.
2. The cold-coated zinc anti-corrosion coating according to claim 1, characterized in that: The modified epoxy resin preparation method is as follows: S2.1: Add epoxy resin to acetone, heat and mix at 60 °C for 1 h to obtain epoxy resin solution, slowly add methyl methacrylate and ammonium persulfate solution to the epoxy resin solution, wherein the volume ratio of methyl methacrylate to ammonium persulfate solution is 80-90:1, and mix by ultrasonic at 80 °C for 6 h to obtain mixture D; S2.2: triethylamine is added to mixture D, wherein the volume ratio of triethylamine to mixture D is 1:80-100, and the mixture is stirred for 30 min. Most of the solvent is removed by vacuum distillation for 1 h to obtain reactant E; S2.3: The reactant E is slowly added to water containing an appropriate amount of emulsifier OP-10, ultrasonically dispersed for 30 min, purified using a high-speed centrifuge at a speed of 800 r / min for 10 min, and filtered using an organic filter membrane to obtain the modified epoxy resin.
3. The cold-coated zinc anti-corrosion coating according to claim 1, characterized in that: The anti-settling agent is natural montmorillonite with a particle size range of 0.2-0.5 μm.
4. The cold-coated zinc anti-corrosion coating according to claim 1, characterized in that: The curing agent is a mixture of a water-based epoxy curing agent AB-HGF and a water-based epoxy curing agent AB-HGA, wherein the volume ratio of the water-based epoxy curing agent AB-HGF to the water-based epoxy curing agent AB-HGA is 2:
3.
5. The cold-coated zinc anti-corrosion coating according to claim 1, characterized in that: The defoaming agent is a polydimethylsiloxane defoaming agent.
6. The cold-coated zinc anti-corrosion coating according to claim 1, characterized in that: The concentration of the phosphoric acid solution in S1.2 is 0.5 M.
7. The cold-coated zinc anti-corrosion coating according to claim 1, characterized in that: The solution C in S1.3 is added to the solution B at a constant flow rate of 1 mL / min.
8. The cold-coated zinc anti-corrosion coating according to claim 2, characterized in that: The concentration of the ammonium persulfate solution in S2.1 is 0.2-0.5 mg / mL.
9. A process for preparing the cold zinc anticorrosive coating according to any one of claims 1 to 8, characterized in that: The specific process of the preparation process of the cold-coated zinc anti-corrosion coating is as follows: S9.1: Add the modified epoxy resin to an appropriate amount of deionized water, stir thoroughly for 1 h to form a uniform modified epoxy resin dispersion, add an anti-settling agent to the modified epoxy resin dispersion, stir uniformly at a speed of 500 r / min for 30 min, and obtain dispersion F; S9.2: Add the modified zinc powder to the dispersion F under stirring conditions, and continue to stir for 30 minutes to obtain a mixed solution G; S9.3: Add the curing agent and defoaming agent to the mixed liquid G according to the formula ratio, and continue stirring for 1 hour to obtain the cold-applied zinc anti-corrosion coating.
10. The preparation process of the cold-coated zinc anti-corrosion coating according to claim 9, characterized in that: The stirring speed in S9.2 is 300 r / min.
Citation Information
Patent Citations
Polyaniline modified metal-ceramic nano coating and preparation method thereof
CN101643607A
Aluminum oxide-containing polyaniline zinc powder flake epoxy heavy anti-corrosion coating and preparation method thereof
CN103834264A